Berberine Inhibits the Release of Glutamate in Nerve Terminals from Rat Cerebral Cortex. - Tzu-Yu Lin; Yu-Wan Lin; Cheng-Wei Lu; Shu-Kuei Huang; Su-Jane Wang (PLoS ONE, 2013)
Berberine, an isoquinoline plant alkaloid, protects neurons against neurotoxicity. An excessive release of glutamate is considered to be one of the molecular mechanisms of neuronal damage in several neurological diseases. In this study, we investigated whether berberine could affect endogenous glutamate release in nerve terminals of rat cerebral cortex (synaptosomes) and explored the possible mechanism. Berberine inhibited the release of glutamate evoked by the K(+) channel blocker 4-aminopyridine (4-AP), and this phenomenon was prevented by the chelating extracellular Ca(2+) ions and the vesicular transporter inhibitor bafilomycin A1, but was insensitive to the glutamate transporter inhibitor DL-threo-beta-benzyl-oxyaspartate. Inhibition of glutamate release by berberine was not due to it decreasing synaptosomal excitability, because berberine did not alter 4-AP-mediated depolarization. The inhibitory effect of berberine on glutamate release was associated with a reduction in the depolarization-induced increase in cytosolic free Ca(2+) concentration. Involvement of the Cav2.1 (P/Q-type) channels in the berberine action was confirmed by blockade of the berberine-mediated inhibition of glutamate release by the Cav2.1 (P/Q-type) channel blocker ω-agatoxin IVA. In addition, the inhibitory effect of berberine on evoked glutamate release was prevented by the mitogen-activated/extracellular signal-regulated kinase kinase (MEK) inhibitors. Berberine decreased the 4-AP-induced phosphorylation of extracellular signal-regulated kinase 1 and 2 (ERK1/2) and synapsin I, the main presynaptic target of ERK; this decrease was also blocked by the MEK inhibition. Moreover, the inhibitory effect of berberine on evoked glutamate release was prevented in nerve terminals from mice lacking synapsin I. Together, these results indicated that berberine inhibits glutamate release from rats cortical synaptosomes, through the suppression of presynaptic Cav2.1 channels and ERK/synapsin I signaling cascade. This finding may provide further understanding of the mode of berberine action in the brain and highlights the therapeutic potential of this compound in the treatment of a wide range of neurological disorders.